Increase in Artemisia annua Plant Biomass Artemisinin Content and Guaiacol Peroxidase Activity Using the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis - Domokos, Erzsébet; Jakab-Farkas, László; Darkó, Béla; Bíró-Janka, Béla; Mara, Gyöngyvér; Albert, Csilla; Balog, Adalbert (Frontiers in Plant Science, 2018)
The main objective of this study was to investigate Artemisia annua plant property variations in terms of plant biomass, glandular trichome numbers, artemisinin production and Guaiacol peroxidase (GPOX) activity when plants are in mutualism with AMF. According to the results, Artemisia annua mutualism with AMF significantly increased the most important and pharmaceutically relevant factors of fresh and dry plant biomass. This increase, especially in the biomass of plant herba (leaves), was 30% higher during the vegetation period and remained high (29% higher than for control) when plants were harvested at the end of the vegetation period. Similar differences in dry biomass were also detected. Glandular trichomas numbers increased by 40%, and the artemisinin content by 17% under AMF colonisation. No effects due to AMF on chlorophyll variations were detected, while Guaiacol peroxidase (GPOX) enzyme concentrations increased significantly under AMF colonization. Altogether the Artemisia plant properties with high pharmaceutically importance (fresh and dry biomass of leaves and artemisinin, number of trichomes and the artemisinin content) were significantly improved by AMF, the application in Artemisia cultivation can be an effective and cheap method. The high GPOX activity under AMF colonization indicate an enhanced oxidative stress alleviation, therefore a higher resistance to water deficiency, mechanisms important under climate conditions with low water supply where Artemisia is usually cultivated.